Variation of ring width and wood density in two unmanaged stands of the Mediterranean oak Quercus faginea - Sousa, Vicelina B. (2018)
Ring width and wood density variation were studied from pith-to-bark and along the stem in two naturally regenerated stands of Quercus faginea Lam. in Portugal. Ring width was significantly different between sites, in both heartwood and sapwood rings, ranging from 1.83 mm to 2.52 mm and from 0.77 mm to 2.11 mm, respectively. Wood density was significantly different between sites only in the heartwood, i.e., 914 kg m3 and 1037 kg m3. Site effects were the main source of variation for ring width and wood density within the heartwood as well as for sapwood ring width, while the between-tree effects explained more the density variation within the sapwood. Wood density showed within-tree uniformity that was not affected by site. The stand characteristics such as basal area and tree age may override the environmental growth conditions. There was also a weak correlation between wood density and ring width components therefore suggesting the possibility of forestry management for both fast tree growth and high wood density